Effect of Winter Dormancy on Three-Dimensional Structure of the Mauthner Neurons in Perccottus glehni Fish - Santalova, Irina M.; Penkova, Nadezhda A.; Mikheeva, Irina B.; Moshkov, Dmitry A. (Problems of Cryobiology and Cryomedicine, 2015)
Investigation of the Mauthner neurons (MN) morphology in fish Perccottus glehni revealed a significant reduction in their volumes during dormancy, probably stipulated by a need to spare the body energy resources. The initial period of winter dormancy was characterized by a decrease in volumes of both main dendrites with no changes in somatic part of MN. During the terminal period of winter dormancy a total volume of soma and lateral dendrite reduced by 50%, and for the ventral one it did by 80%. It can be assumed that a decrease in integral neuronal volumes is associated with developing hypometabolism, as well as with a significantly decreased inputs of afferent information, entering MN from auditory and visual analyzers. Probl Cryobiol Cryomed 2015; 25(2): 114-121